STRATEGI KOMUNIKASI MARKETING IKLAN DI RADIO SAFASINDO 98,2 FM KOTA PAYAKUMBUH - Ronaldo Ronaldo; Muhamad Fafjri (KOLONI, 2023)
Radio is one of the electronic media that has long been known and still survives today. Although currently many other media have sprung up, and are able to provide information and entertainment, the technology used is quite sophisticated, but radio still has its own charm for its listeners. Radio is a medium of information and entertainment that is cheap and practical and easy to hear anytime and anywhere. Radio itself is also inseparable from advertising, without advertisers advertising their products on radio, radio cannot survive and operate, especially for private radio, because advertisers are the most important part of radio. Based on this, this thesis examines how the advertising marketing strategy used on Safasindo 98.2 FM radio in getting advertisers, the strategies used in finding advertisers are intensive, diversification and integration strategies. This study used a qualitative approach using descriptive methods using several steps, namely: observation of data collection was carried out by means of structured interviews, and documentation. This study concludes that in finding and retaining advertisers, Safasindo 98.2 FM radio prioritizes programs that are broadcast on the radio. An interesting program will be an attraction for radio to promote advertisements on radio. Keywords: Strategy, Communication, Marketing, Advertising, Radio